Answer:
NAN
Explanation:
x + 2 = 3x - x^2 Simplifying x + 2 = 3x + -1x2 Reorder the terms: 2 + x = 3x + -1x2 Solving 2 + x = 3x + -1x2 Solving for variable 'x'. Combine like terms: x + -3x = -2x 2 + -2x + x2 = 3x + -1x2 + -3x + x2 Reorder the terms: 2 + -2x + x2 = 3x + -3x + -1x2 + x2 Combine like terms: 3x + -3x = 0 2 + -2x + x2 = 0 + -1x2 + x2 2 + -2x + x2 = -1x2 + x2 Combine like terms: -1x2 + x2 = 0 2 + -2x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '-2' to each side of the equation. 2 + -2x + -2 + x2 = 0 + -2 Reorder the terms: 2 + -2 + -2x + x2 = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -2x + x2 = 0 + -2 -2x + x2 = 0 + -2 Combine like terms: 0 + -2 = -2 -2x + x2 = -2 The x term is -2x. Take half its coefficient (-1). Square it (1) and add it to both sides. Add '1' to each side of the equation. -2x + 1 + x2 = -2 + 1 Reorder the terms: 1 + -2x + x2 = -2 + 1 Combine like terms: -2 + 1 = -1 1 + -2x + x2 = -1 Factor a perfect square on the left side: (x + -1)(x + -1) = -1 Can't calculate square root of the right side. The solution to this equation could not be determined.